Internalization of Islamic Economic Values in Digital Literacy Education and Entrepreneurial Ethics in Arab Society - Wijonarko, Wijonarko; Barkah, Qodariah; Sumantri, Rinol; Hilda, Hilda (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2025)
The purpose of this study is to briefly analyze the strategies, challenges, and impacts of internalizing Islamic economic values in improving digital literacy and shaping entrepreneurial ethics based on the values of justice (al-‘adl), honesty (al-sidq), trustworthiness, and benefit (al-maslahah). This study discusses the internalization of Islamic economic values in the development of digital literacy and entrepreneurial ethics through an Islamic values education approach in the Arab community in Palembang City. This study is motivated by the importance of digital literacy as a means of economic empowerment for Muslim communities in the era of technological transformation, as well as a medium for learning Islamic values and morality in business activities. This research is qualitative with a phenomenological approach; the research data were obtained from in-depth interviews with 15 informants, consisting of business actors, community leaders, and consumers, supplemented by participatory observation and documentation of the digital activities of the business community. The analysis was conducted interactively using the Miles and Huberman model with reduction, presentation, and conclusion drawing, as well as triangulation of sources and methods to ensure validity. The results show that the level of digital literacy among business actors varies, influenced by factors such as generation, social trust, and community support. The internalization of Islamic economic values has been proven to strengthen ethical awareness, increase consumer trust, and encourage fair and sustainable entrepreneurial behavior. This study contributes to the development of a digital literacy-based Islamic values education model that integrates business ethics and entrepreneurial spirituality.